Albright & Wilson and Change in the Quaker Business Environment During World War I. Issue 2 (December 2019) - Sleapwood, Nicola
Abstract : This article uses the example of Albright & Wilson, a chemical manufacturing firm based in Birmingham, to highlight the potential impact of war, and World War I specifically, on Quaker businesses. Using principally archival records, it provides some background to the Quaker pacifist debate of the time, as well as to the directorial and managerial structure of the firm. Having provided a thorough analysis of key figures and control in the firm, it argues that, in bringing the pacifist question to a head, as well as in creating commercial difficulties, World War I led to the firm ceasing to be Quaker in any recognisable sense. The examples of Clark, Son & Morland and Baker and Sons are used to suggest that this was a broader trend in Quaker businesses at this time.